Evaluation of the Implementation of Augmented Reality on Vegetable Objects Using Marker-Based Tracking and SUS - Adrian Putradinata, Gusti Made; Ashari, Ilham Firman; Nugroho, Eko Dwi (Department of Electrical Engineering, 2025)
With the rapid development of technology in the field of information media, which initially received information from mass media, schools, electronic media and the development of Augmented Reality technology that can be applied to the field of information. Augmented Reality is the incorporation of two-dimensional virtual objects into a real environment. AR has many benefits in the field of entertainment and others. The purpose of this study is to implement information media in the form of augmented reality with a Marker-based tracking approach on leaf vegetable objects using markers in the form of paper and can display information in virtual objects, namely the content and benefits, processing of vegetables that appear as objects, producing markers that can be detected with several tests of distance, light, and marker resistance. At a distance of 10 cm – 50 cm the marker can be detected using both smartphones (Vivo and Samsung), but at a distance of 100 cm samsung smartphones are no longer able to detect due to camera differences. Marker light testing can be detected at 5 – 200 Lux light but in >1 lux marker cannot be detected and displays objects. The usability test uses the System Usability Scale (SUS) method which results in a final score of 71,583 which means that the system that has been developed is already feasible to give to users.